Purificação de substâncias antibacterianas e estudo de plasmídios colicinogênicos de Shigella sonnei - Jaqueline Silvana Moreira (2018)
Shigellais the etiological agent of shigellosis a worldwide distributed severe type of inflammatory diarrhea. The disease affects about 165 million people and it is responsible for nearly 1 million deaths mainly of children from developing countries 5each year. Antimicrobialpeptides and/or proteins are biologically active substances, produced by prokaryotes and eukaryotes.The expression of these substances may contribute to the defense of the producer organismagainst pathogens and may also represent a competitive advantage to it.Our research group investigates the production of antimicrobial peptides and/or proteins, in special, bacteriocins. The aim of this 10investigation was to isolate and identify antibacterial substances and to evaluate the presence of colicinogenic plasmids in a sample of Shigella sonnei. For purification and identification, the biomolecules were extracted from the intracellular fraction by protein precipitation employing ammonium sulfate 30-75 % (C-75), purified by sequential chromatographic steps,evaluated about antagonistic action against another isolate of 15the same species, analyzed for purity, and sequenced by mass spectrometryand compared with available in databases.The identification of the colicinogenic plasmids was performed by extracromossomic DNA extraction,construction of DNA libraries, next-geration sequencer analysis, identification of the ORFs for comparison in databases, transfer of the colicinogenic plasmids by conjugation and transformation, 20confirmation of the antagonistic action produced by the transconjugant and transformant isolates and polyacrylamide gel analyzes.Purification and sequencing assays identified seven antibacterial substances and among them a histone-like protein and a ribosomal hibernation factor protein. Genetic sequencing identified the presence of two colicinogenic plasmids, encoding a colicin with a molecular mass of 61.2kDa and colicin 25E1. The data show that S. sonneiproduces several bioactive substances that can aid in the processes of infection, colonization and nutrients.